1958
DOI: 10.1103/physrev.110.1286
|View full text |Cite
|
Sign up to set email alerts
|

Hall and Transverse Magnetoresistance Effects for Warped Bands and Mixed Scattering

Abstract: Evaluation of the transport integrals for warped bands using the method of McClure was done for relaxation times determined by mixed scattering from acoustic phonons and ionized impurities. Hall and transverse magnetoresistance coefficients were calculated for parameters characteristic of the degenerate valence bands in germanium and silicon, as obtained from cyclotron resonance data. For germanium, results are consistent with observation in regard to a density-of-states ratio for fast and slow holes of approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1961
1961
1975
1975

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…This small reduction could easily be overlooked without the supporting data at larger Sb/Ga ratios. It is seen that ~H/~ is about 1.2 for this sample, which is much the same as for p-type germanium (11). The hole concentration, p, and melt composition from which the crystal was prepared are shown.…”
Section: Journal Of the Electrochemical Societysupporting
confidence: 54%
“…This small reduction could easily be overlooked without the supporting data at larger Sb/Ga ratios. It is seen that ~H/~ is about 1.2 for this sample, which is much the same as for p-type germanium (11). The hole concentration, p, and melt composition from which the crystal was prepared are shown.…”
Section: Journal Of the Electrochemical Societysupporting
confidence: 54%
“…Initially the theory was brought in qualitative agreement with observations when both heavy-and light-hole conduction was considered [ 11. However, a detailed description of the structure in the magnetic field dependence of the Hall coefficient was not arrived at until warping of the heavy-hole band and mixed scattering of acoustical phonons and impurities was taken into account [2]. This is, a t present, the state of the current theory which is in fair agreement with observed galvanomagnetic phenomena a t comparatively low temperatures.…”
Section: Introductionmentioning
confidence: 94%
“…It is found that the value of is greater than the value of ,kI2 in every case (as for thin samples also) indicating that ionized impurity scattering is greater for light holes than for heavy holes. Beer and Willardson [5] have also found that /I1 is greater than /Iz from their dc measurement of galvanomagnetic properties on p-type Ge. It is evident from Table 2 that (zl) for light holes is smaller as compared to (zz) for heavy holes.…”
Section: Experimental Results and Comparison With Theorymentioning
confidence: 93%
“…5 cm. The sample parameters along with their designation number are given in Table 1. T a b l e 1 Samples designation and parameters 1 carrier sample NO.…”
Section: Experimental Results and Comparison With Theorymentioning
confidence: 98%